Impact of Trade Development in Poverty Reduction in Nepal (Cognition, 2019)
Trade is essential for economic development, employment creation and poverty reduction of the country. It is necessary to look forward towards the import and export sector of the country for prosperous economic growth. Nepal has undertaken extensive trade liberalization since 1990. The volume of World Trade in terms of goods and services increased by 2.2 percent in 2016 and reached around 3.8 percent in 2017. The World economy increased by 3.6 percent in 2018 and is expected to grow by 3.3 percent in 2019. The GDP at basic price increased by 6.3 percent in 2018 and it is estimated to increase by 6.8 percent in 2019. Similarly GDP at producer price was 6.7 percent in the 2018 and 7.0 percent in 2019. The contribution of non-agriculture sector to GDP is estimated to be 73 percent in 2018/19. Due to improvement in trade and services, the non-agriculture sector is estimated to expand by 7.5 percent in 2018/19. In Nepal, the first trade policy was introduced in 1983 with the slogan “Exports for Development”. Also a new trade policy was brought in 1992. Due to changes in development and growth, trade policy was again revised in 2009. Various challenges were faced in order to decrease poverty and increase economic growth so the government introduced a new trade policy, 2015. The poverty reduced to 42 percent in 1996 against 31 percent in 2004 and 25.2 percent in 2011. Similarly, per capita income is increased by 1.7 percent and poverty is decreased by 1.4 percent every year. This study therefore focuses on the contribution of each sector to maintain balance in trade. Export oriented growth is the concrete impact on poverty reduction.